Investigating the Effect of Fluid Substitution on AVO Response: A Physical Modelling Study. Issue 1 (1st December 2019) - Moravej, Kamal; Malcolm, Alison
Summary: Seismic physical modelling is a powerful method for verification of different algorithms and also for better understanding wave propagation phenomenon. In this paper, we design a physical model made out of Plexiglas to investigate the effect of fluid substitution on Amplitude Variation with offset (AVO) by designing a physical model in a way that remove the influence of other factors that can impact the AVO behavior. We record the seismic response of two scenarios, one that is representative of dry/gas saturated medium and another one is the representative of water saturated medium. After processing of recorded seismic data and picking the reflection amplitude, we implement some corrections over the reflection amplitude to represent true reflectivity. The corrected amplitude of both cases were used to extract Intercept ( R 0) and Gradient (G) AVO attributes based on the Shuey equation. The extracted values are mapped on R 0 − G cross-plot. From the cross-plot, it is clear that the substitution of water with gas is resulted in shifting the position of point toward the center of the cross-plot.